Health seeking behavior of migrant and non-migrant spouse towards HIV/AIDS in kailali district. - Khadka, Dan Bahadur (2008)
ABSTRACT: The study has attempted to find out the health seeking behavior of the spouse of migrant and spouse of non-migrants towards the HIV/AIDS. Most of the migrants are dalits. Majority of people are dependent on agriculture and most females are illiterate or have acquired primary education only. Due to lack of job opportunity, own agricultural land people of have visit India to seek Job. In India they used to work as factory labor, watch man, security guard, driver etc. During their stay at India they perform unsafe sexual practice and they are vulnerable to acquire the disease and finally transmitted to their wives. The study is concerned with two hundred respondents; hundred from each group. It is found that nearly 800-1000 people visit India per year from the VDC. Mostly the people of age 20-35 years visit India to seek the job. Early marriage occurs in spouse of migrant than that of non-migrant. In the age group 15-19 yrs. there are 6% respondents from spouse of migrant but there are only 1% respondents in the non-migrant group. Regarding the ethnicity, there are only 9% Brahmins, 36% Chhetri, 1% Newar and 54% are other ( Nepali, Damai, Kami, Sarki, Tikatari etc.) in migrant group but there are only 22% other (Nepali, Damai, Kami, Sarki, Tikatari etc.) in the non-migrant group. This shows that more dalits belongs to migrants and the respondents in both the group are house wives. The spouses of migrants were more illiterate than those of non-migrant. Again there are 22 respondents from the non migrant who completed secondary level education but there are no any respondents from spouse of migrant to complete the secondary level education. But spouse of migrant poses good knowledge than that of non-migrant regarding the disease transmission and preventive measures. This might be due to more programs of various agencies are concerned with migrants. Out of the total respondents in both the group 70% respondents of migrant group and 85% respondents of non-migrant group visit the PHC at first to seek the advice regarding the disease. While more spouse of migrant visit FCHVs than those of non-migrant because the FCHVs are more focused on spouse of migrant regarding HIV/AIDS than spouse of non-migrants.The participation of respondents on discussion about the HIV/AIDS, 75% spouse of migrants attended while 36% spouse of non-migrants attended the discussion and their satisfaction about the discussion; most of the participants were satisfied. To view categorically spouse of migrant are more satisfied than spouse of non-migrants because spouse of non-migrant felt that the program is not concerned with them. Majority of the respondents to seek the service regarding the disease were the spouse of migrants that is 39% were spouse of migrants where as only 7% spouse of non-migrants. Almost all the respondents from both the checked their blood for HIV only one time but one respondent from spouse of migrant check her blood for two times but no any respondent from non-migrant group checked their blood for twice. It is found that 100% respondents were satisfied with the services by the health institutions for checking blood to detect HIV/AIDS. Out of total respondents only 18% respondents have heard of VCT because there is no any VCT center run by government at local level. All the respondents replied that there is medicine for HIV/AIDS and they replied that medicine is found in the hospitals. 97% respondents replied that the disease is not cured completely by the available medicine but 3% did not know about the medicine. So all the spouse of migrants and spouse of non-migrants are well informed about the medicine of the disease. It is found that migrants marry earlier than non-migrants due to which male members have to bear greater responsibility of family. They have to make money to feed their family and ultimately they visit India. This is the main cause of transmission of disease across the boarder. There are various supporting organizations in the VDC to create awareness about the disease and educating the people about the mode of transmission, preventive measures, treatment etc. These efforts have made great impact to generate the awareness about the disease but they are not so effective to control the problem. So until and unless the underlying causes i.e. poverty, lack of job opportunity etc. are not addressed along with the preventive and curative programs, the disease will remain as time bomb in the community. Thus there should be coordinated efforts from the multiple sectors to address the problem correctly and timely.